A study on the transport and interaction between blood flow and low-density-lipoprotein in near-wall regions of blood vessels. Issue 13 (3rd October 2021) - Choudhury, Satyajit; Anupindi, Kameswararao; Patnaik, B. S. V.
Abstract: Differences in the dynamics and transport of blood make certain regions of the arterial network the preferred sites for initiation and formation of arterial diseases like stenosis and aneurysms. Understanding of such arterial diseases is directly linked to critical hemodynamic parameters such as the wall shear stress (WSS). The present work generalises the influence of WSS on the concentration of LDL that was observed in an earlier study. To this end, a wide variety of simplified flow domain, inspired by the near-wall regions of aneurysms and stenosis, are constructed and analyzed. The effects of pulsatile inflow condition, rheology of blood and curvature of the wall on the correlation between WSS and LDL concentration are investigated. It is demonstrated that the time-scale of variation of lumen-surface-concentration (LSC) of LDL is larger than a single cardiac cycle. As a consequence, the time-average values of WSS are sufficient to locate the regions of higher LSC. This idea is strengthened by making use of simplified flow domain that generates moving stagnation point. Further, it was observed that the rheology of the blood and curvature of the wall does not affect the observed correlation between the WSS and LDL concentration.